Refeeding day strategies in elite soccer players: a new way to maintain performance losing body fat percentage - Fernandes, H. (Journal of Clinical and Biomedical Investigation, 2023)
The refeeding days strategies are already used by bodybuilders in pre-contest periods to increase the decrease in body fat percentage without impairing the performance of these athletes and maintain fat-free mass for their competition day. But, among elite soccer players, who always want to have low percentages of body fat, how could the refeeding days strategies be used? Perhaps in off-season periods where there is not so much concern in optimizing performance but in keeping the fat-free mass high and reducing the body fat percentage. This work demonstrates a scientifically based commentary with articles that address the subject and a proposal of how the prescription of a dietary week that includes refeeding days strategies for elite soccer players who want to reduce body fat percentage during off-season periods could be.